2020
DOI: 10.3390/su12219120
|View full text |Cite
|
Sign up to set email alerts
|

Should Photovoltaics Stay at Home? Comparative Life Cycle Environmental Assessment on Roof-Mounted and Ground-Mounted Photovoltaics

Abstract: Renewable energy technologies like photovoltaics may be considered an indispensable component of a low-carbon electricity mix, but social acceptance should not be taken for granted. For instance, in Greece there are still claims, especially in rural areas, regarding the land use and the competition against more traditional economic activities such as grazing. An argument in favor of confining to roof-mounted photovoltaic installations is the additional infrastructure requirements for ground-mounted larger-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…(2) PV modules attached to a roof [22]; and (3) PV modules integrated in a roof (or a greenhouse roof) [23]. Agrivoltaic systems have been studied in multiple countries such as Germany, Japan, China, United States, France, Chile, and South Korea [14,[17][18][19].…”
Section: Roof Building Integrated Photovoltaics For Agrivoltaic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) PV modules attached to a roof [22]; and (3) PV modules integrated in a roof (or a greenhouse roof) [23]. Agrivoltaic systems have been studied in multiple countries such as Germany, Japan, China, United States, France, Chile, and South Korea [14,[17][18][19].…”
Section: Roof Building Integrated Photovoltaics For Agrivoltaic Systemsmentioning
confidence: 99%
“…The roof BIPV has three different classifications: (1) PV modules on a rooftop [21]; (2) PV modules attached to a roof [22]; and (3) PV modules integrated in a roof (or a greenhouse roof) [23]. PV modules on a rooftop (i.e., rooftop PVs) are traditional rooftop PVs taking 80% of the BIPV market [3].…”
Section: Roof Building Integrated Photovoltaics For Agrivoltaic Systemsmentioning
confidence: 99%
“…At present, the research on centralized photovoltaic power generation mainly focuses on the cost of electricity [5], benefit analysis and evaluation [6], power generation efficiency [7,8], carbon emission [9], environmental impact [10], and so on, and there is little research on the influencing factors and their mechanism of cost control in the whole life cycle of centralized photovoltaic power generation. Mustafa et al [11] identified the key factors that affect the implementation of photovoltaic power generation projects through multiple linear regression models (MLRMs) and rule-based decision support systems (RBDSSs).…”
Section: Introductionmentioning
confidence: 99%
“…Each credit can have a certain number of points. By adding up all these points, LEED projects can achieve one out of four certifications: certified (scores [40][41][42][43][44][45][46][47][48][49], silver (scores 50-59), gold (scores 60-79), or platinum (scores 80+) (Section 1.2 provides a summary of all prerequisites and credits for LEED-NC v3).…”
Section: Introduction 1leed Certification Strategies In Different Cou...mentioning
confidence: 99%